A nanoporous MXene film enables flexible supercapacitors with high energy storage. Issue 20 (14th May 2018) - Fan, Zhimin; Wang, Youshan; Xie, Zhimin; Xu, Xueqing; Yuan, Yin; Cheng, Zhongjun; Liu, Yuyan
Abstract : A simple strategy is developed to prepare a nanoporous MXene film with high volumetric capacitance and good rate capability. Abstract : MXene films are attractive for use in advanced supercapacitor electrodes on account of their ultrahigh density and pseudocapacitive charge storage mechanism in sulfuric acid. However, the self-restacking of MXene nanosheets severely affects their rate capability and mass loading. Herein, a free-standing and flexible modified nanoporous MXene film is fabricated by incorporating Fe(OH)3 nanoparticles with diameters of 3–5 nm into MXene films and then dissolving the Fe(OH)3 nanoparticles, followed by low calcination at 200 °C, resulting in highly interconnected nanopore channels that promote efficient ion transport without compromising ultrahigh density. As a result, the modified nanoporous MXene film presents an attractive volumetric capacitance (1142 F cm −3 at 0.5 A g −1 ) and good rate capability (828 F cm −3 at 20 A g −1 ). Furthermore, it still displays a high volumetric capacitance of 749 F cm −3 and good flexibility even at a high mass loading of 11.2 mg cm −2 . Therefore, this flexible and free-standing nanoporous MXene film is a promising electrode material for flexible, portable and compact storage devices. This study provides an efficient material design for flexible energy storage devices possessing high volumetric capacitance and good rate capability even at a high mass loading.